Rapid Detection of Equine Piroplasms Using Multiplex PCR and First Genetic Characterization of Theileria haneyi in Egypt - Elsawy, Bassma S. M.; Nassar, Ahmed M.; Alzan, Heba F.; Bhoora, Raksha, V; Ozubek, Sezayi; Mahmoud, Mona S.; Mahdy, Olfat A. (Mdpi, 2021)
Equine Piroplasmosis (EP) is an infectious disease caused by the hemoprotozoan parasites Theileria equi, Babesia caballi, and the recently identified species T. haneyi. Hereby, we used a multiplex PCR (mPCR) targeting the 18S rRNA gene of T. equi and B. caballi for the simultaneous detection of EP in Egyptian equids and examined the presence of T. haneyi infections in Egypt. Blood samples from 155 equids (79 horses and 76 donkeys) collected from different governorates of Egypt were examined by mPCR and PCR targeting T. hayeni. The mPCR method revealed a prevalence of T. equi of 20.3% in horses and of 13.1% in donkeys and a prevalence of B. caballi of 1.2% in horses. B. caballi was not detected in donkeys in the current study. The mPCR method also detected coinfections with both species (2.5% and 1.3% in horses and donkeys, respectively). Additionally, we report the presence of T. haneyi in Egypt for the first time in 53.1% of the horse and 38.1% of the donkey tested samples. Coinfection with T. haneyi and T. equi was found in 13.5% of the samples, while infection with the three EP species was found in 1.9% of the samples.
Keywords: equids; Babesia caballi; Theileria equi; Theileria haneyi; multiplex PCR; cPCR; 18S rRNA gene and sequencing